ANALISIS PEMBIAYAAN DENGAN SISTEM SYARIâ€™AH DAN PEMBINAAN HUBUNGAN KERJA TERHADAP PENINGKATAN PENDAPATAN PENGUSAHA KECIL - Malikah, Anik (Fakultas Ekonomi, UIN Maliki Malang, 2011)
The purpose of this study is to know how the effect of fund to Syariâ€™ah system and construction of work relation to the increasing of small entrepreneur earnings. on actual events than people perception about an event. The population of this research is costumers who gain funds from Pusat Pendanaan Syariâ€™ah (PPS) or Syariâ€™ah This research is empirical study that is â€an approach to gain knowledge, which separate between obtained knowledge based on fact and knowledge without factâ€ or it is more emphasized Fund Center of Economic. The number of population is 200 customers. However, the sample taking method uses sampling purposive method. The sample of customers that are chose is 40 customers. The data is analyzed by using double linier regression. The analysis result of this study shows that funding by using syariah system which is owned by PPS and constructions of work relation influence significantly to increase small entrepreneur earnings. Besides PPS has important role in helping small entrepreneur to increase its earnings through funding and constructing work relation.